2004
DOI: 10.3171/jns.2004.100.3.0414
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of multiple intraarterial papaverine infusions for improvement in cerebral circulation time in patients with recurrent cerebral vasospasm

Abstract: The preliminary results indicate that multiple intraarterial papaverine treatments consistently improve cerebral circulation times, even with repeated infusions in cases of recurrent vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…8,10,12,14,17,26,27,34,35,42,45,46,49,58 Liu, et al, 34 reported clinical improvement in 12 (71%) of 17 patients; eight patients had improvement of depressed level of consciousness, one had reversal of upper-extremity weakness, and three had improvement of vasospasm-induced aphasia. In a review of the literature by Hoh and Ogilvy, 23 clinical improvement after papaverine infusion was demonstrated in 148 (43%) of 346 patients.…”
Section: Clinical Effects and Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…8,10,12,14,17,26,27,34,35,42,45,46,49,58 Liu, et al, 34 reported clinical improvement in 12 (71%) of 17 patients; eight patients had improvement of depressed level of consciousness, one had reversal of upper-extremity weakness, and three had improvement of vasospasm-induced aphasia. In a review of the literature by Hoh and Ogilvy, 23 clinical improvement after papaverine infusion was demonstrated in 148 (43%) of 346 patients.…”
Section: Clinical Effects and Outcomesmentioning
confidence: 99%
“…ter; 8,37 to improve CBF by dilating the proximal, intermediate, and distal cerebral arteries; 8 to improve mean cerebral circulation time; 34,36 and to improve cerebral oxygenation.…”
Section: Clinical Effects and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations